CLINICAL AND LABORATORY PARAMETER ANALYSIS IN PATIENTS WITH COMMON VARIABLE IMMUNODEFICIENCY - Krtinić, Danka (Medicinski podmladak, 2022)
Introduction: Common Variable Immunodeficiency (CVID) is the most prevalent primary immunodeficiency in adult population. The diagnosis is based on low concentration of at least 2 immunoglobuline classes, mostly IgG, with low IgA and/or IgM. Beside recurrent infections, patients with CVID usually suffer from different respiratory, gastrointestinal, autoimmune and malignant diseases. Leading therapeutic approach to managing CVID is regular intravenous (IVIG) and subcutaneous (SCIG) immunoglobulin replacement therapy. Therefore, the aim of our study was to analyze clinical and laboratory parameters in patients with CVID. Material and Methods: The present study included 24 patients with CVID who were treated at Clinic of Allergy and Immunology, University Clinical Center of Serbia from 2012 to 2022. Demographic data, clinical and laboratory parameters were obtained from the patients’ medical records. IgG, IgM and IgA concentrations were measured by nephelometry. Statistical analysis was performed using descriptive methods, Student t test for independent samples and Fisher exact test. Results: Respiratory manifestations were found in 70.8% of patients, gastrointestinal in 45.8%, autoimmune in 29.2% and malignancies in 20.8%. The presence of autoimmune diseases was the most common within the patients aged between 20 to 30 years, and it was statistically significantly higher comparing to other age groups (p=0.014). Serum IgG concentration of 7.6±2.7 g/l was measured. Statistically significantly higher IgG concentrations were observed in patients receiving SCIG (10.2±1.6) compared to those receiving IVIG (6.7±2.4) (t=-3.3, p=0.003). Premedication was required in 44.4% of patients receiving IVIG. Conclusion: The most common complication of CVID are chronic lung diseases. Autoimmune diseases are the most frequently diagnosed in patients between the ages of 20 and 30. The use of SCIG is identified as better form of immunoglobulin replacement therapy. Total immunoglobulin serum concentration measuring in patients with recurrent infections and autoimmune diseases can contribute to timely diagnosis.